MANAGEMENT AND FETAL OUTCOMES OF SECOND STAGE FETAL COMPROMISE: A CROSS-SECTIONAL ANALYSIS AT THE GYNECOLOGY DEPARTMENT. : JPUMHS;2024:14:04,267-275. http://doi.org/10.46536/jpumhs/2024/14.04.587 - Nusrat Fozia Pathan1, Bushra Noor Khuhro2, Kainat3, Shahzadi Pir4, Rashida Akbar Ghumro5, Afra Rehman6 Aqsa7. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Second-stage fetal compromise is a critical obstetric emergency that requires prompt intervention to prevent adverse neonatal outcomes. Prolonged second-stage labor, fetal distress, and maternal exhaustion contribute to fetal hypoxia, leading to increased morbidity and mortality. Effective management strategies, including operative vaginal delivery and emergency cesarean section, play a crucial role in optimizing fetal outcomes. OBJECTIVES: This study aims to evaluate the management approaches and fetal outcomes in cases of second-stage fetal compromise. Specific objectives include identifying risk factors, assessing different intervention strategies, and analyzing neonatal outcomes such as Apgar scores, NICU admissions, and perinatal mortality. METHODS: A cross-sectional study was conducted at the Gynecology Department, analyzing 220 cases of second-stage fetal compromise. Data were collected from medical records, including maternal demographics, fetal heart rate monitoring, mode of delivery, and neonatal outcomes. Statistical analysis was performed using SPSS, applying chi-square and logistic regression tests to determine associations between management strategies and fetal outcomes. RESULTS: Among the 220 cases, 60% underwent emergency cesarean section, 30% required instrumental delivery forceps/vacuum, and 10% had spontaneous vaginal delivery. Neonatal outcomes showed that Apgar scores ≤ 7 at 5 minutes were observed in 25% of cases, while NICU admission was required in 18%. Perinatal mortality was 4%, primarily associated with prolonged fetal distress. Emergency cesarean section was significantly associated with improved neonatal outcomes p < 0.05. CONCLUSION: Timely identification and appropriate management of second-stage fetal compromise significantly improve neonatal outcomes. Emergency cesarean section remains the most effective intervention in severe cases. Strengthening intrapartum monitoring and decision-making can further enhance fetal survival rates.